2020
DOI: 10.7554/elife.52283
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule G-quadruplex stabilizers reveal a novel pathway of autophagy regulation in neurons

Abstract: Guanine-rich DNA sequences can fold into four-stranded G-quadruplex (G4-DNA) structures. G4-DNA regulates replication and transcription, at least in cancer cells. Here, we demonstrate that, in neurons, pharmacologically stabilizing G4-DNA with G4 ligands strongly downregulates the Atg7 gene. Atg7 is a critical gene for the initiation of autophagy that exhibits decreased transcription with aging. Using an in vitro assay, we show that a putative G-quadruplex-forming sequence (PQFS) in the first intron of the Atg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 89 publications
1
80
0
Order By: Relevance
“…92 Pif1 has also been overexpressed in cells to reverse G4-mediated genetic instability in S. cerevisiae, 247 repair dysfunctions in cancer cells 248 and cognitive dysregulations in neurons. 249 In the latter two examples, Pif1 overexpression was found to remedy phenotypes of G4-mediated functional impairment induced by G4-stabilising PDS treatments. Similarly, BLM was overexpressed to reverse reactive oxygen species (ROS)-induced G4 (and R-loop) formation at transcriptionally active sites, thus restoring the repair process.…”
Section: The Dna Damage Response (Ddr)mentioning
confidence: 99%
“…92 Pif1 has also been overexpressed in cells to reverse G4-mediated genetic instability in S. cerevisiae, 247 repair dysfunctions in cancer cells 248 and cognitive dysregulations in neurons. 249 In the latter two examples, Pif1 overexpression was found to remedy phenotypes of G4-mediated functional impairment induced by G4-stabilising PDS treatments. Similarly, BLM was overexpressed to reverse reactive oxygen species (ROS)-induced G4 (and R-loop) formation at transcriptionally active sites, thus restoring the repair process.…”
Section: The Dna Damage Response (Ddr)mentioning
confidence: 99%
“…We recently investigated whether pharmacologically stabilizing G4-DNA with pyridostatin (PDS) [34], a selective G4-binding small molecule (referred to as a G4-ligand [35]), affects neuronal autophagy. Using circular dichroism spectroscopy (CD), thermal difference spectra (TDS) and nuclear magnetic resonance (NMR) analyses, we demonstrated that a putative G4-DNA forming sequence (PQFS) identified in the Atg7 gene folds into a stable G4 structure in vitro, which PDS strongly binds to [33]. We next showed that the G4-specific antibody (HF2) and the G4-binding protein SUB1/PC4 bind to the Atg7's PQFS ( Fig.…”
mentioning
confidence: 99%
“…The Atg7 gene (human, mouse, rat) contains numerous putative G4-forming motifs [33]. We recently investigated whether pharmacologically stabilizing G4-DNA with pyridostatin (PDS) [34], a selective G4-binding small molecule (referred to as a G4-ligand [35]), affects neuronal autophagy.…”
mentioning
confidence: 99%
“…The study of human PIF1 (hPIF1) has also demonstrated the deleterious consequences of Pif1 helicase misregulation. The transfection of cultured primary neurons with hPIF1 is toxic, increasing the risk of cell death (80). Further, human tumor cells rely on hPIF1 for protection from apoptosis (81), whereas hPIF1 depletion in normal cells increases replication fork arrest (82).…”
Section: Discussionmentioning
confidence: 99%